Human Factor:reliability production system instabilities - Borges, Fabio Morais; Menegon, Nilton Luiz (Revista Gestão da Produção Operações e Sistemas, 2012)
Ensure reliability of production systems is a goal constantly sought by companies. Greater focus is usually given to technical issues. However, the guarantee of continued operation of these systems also passes through the human system. And more than that, the restoration of normal operation when there is variability in the system the human factor role is often decisive because the technical characteristics don’t have some human characteristics as common sense, anticipation, perception, among others. It becomes, in this paper, a theoretical argument about the human factor as a source of reliability of production systems, listing the conditions for that to become possible. To illustrate the concepts and ideas put forward, some situations are presented in a refinery, where the complexity and danger of the system require a higher degree of reliability than other production systems. The article presents the reflections that lead to think the human factor as the active maintainer of system reliability and not as a simple vigilant of the premises.Keywords: Human reliability, human factor; production facilities